APPLICATION OF INSTRUMENTAL NEUTRON ACTIVATION ANALYSIS ON ICE CORE SAMPLES - BACCOLO, GIOVANNI; Clemenza, Massimiliano; Delmonte, Barbara; Maffezzoli, Niccolò; Maggi, Valter; Previtali Ezio (2014)
A first application of INAA (Instrumental Neutron Activation Analysis) to ice core samples